2020
DOI: 10.3390/jcm9124011
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Association of Acquired Human Cytomegalovirus Infection with Hearing Loss

Abstract: Congenital cytomegalovirus (CMV) infection induces a clinical syndrome usually associated with hearing loss. However, the effect of acquired CVM infection in adults and children has not been clearly defined. The objective of this review is to critically appraise scientific evidence regarding the association of acquired CMV infection with postnatal hearing loss or tinnitus. A systematic review of records reporting sensorineural hearing loss (SNHL) or tinnitus and acquired CMV infection including articles publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It is widely reported that uterine TORCH infections have risk factors for hearing loss to develop in children. In particular, the degree of hearing impairment caused by CMV infection is correlated with the viral load and the trimester of mother infection [24] .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that uterine TORCH infections have risk factors for hearing loss to develop in children. In particular, the degree of hearing impairment caused by CMV infection is correlated with the viral load and the trimester of mother infection [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for both CMV and rubella virus infections, infants presenting with systemic, symptomatic infection reflecting disseminated infection are more likely to progress to severe or profound hearing loss [ 76 , 77 ]. Notably, CMV and rubella virus infection acquired postnatally have not been found to cause hearing loss [ 78 , 79 ], suggesting that prenatal cochlear development is particularly sensitive. Importantly, different congenital infections also appear to cause hearing loss via disparate mechanisms.…”
Section: The Cochlea As a Model Organ To Study The Effect Of Early Life Inflammation On The Developing Hematopoietic And Immune Systemsmentioning
confidence: 99%
“…Congenital CMV infection is currently estimated to be the leading non-genetic cause of SNHL [ 17 ]. Conversely, postnatal CMV infection is not recognized as a direct cause of SNHL in the pediatric population [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%